Predicting later problematic cannabis use from psychopathological symptoms during childhood and adolescence: results of a 25-year longitudinal study - Zohsel, Katrin; Schmidt, Martin H.; Banaschewski, Tobias; Laucht, Manfred (Drug and alcohol dependence, 2016)
Background - Cannabis is the most commonly used illegal substance among adolescents and young adults. Problematic cannabis use is often associated with comorbid psychopathological problems. The purpose of the current study was to elucidate the underlying developmental processes connecting externalizing and internalizing psychopathology in childhood and adolescence with problematic cannabis use in young adulthood. - Methods - Data were drawn from the Mannheim Study of Children at Risk, an ongoing epidemiological cohort study from birth to adulthood. For n=307 participants, symptom scores of conduct/oppositional defiant disorder, attention problems, hyperactivity/impulsivity, and internalizing disorders were available for the periods of childhood (4.5-11 years) and adolescence (15 years). At age 25 years, problematic cannabis use was assessed via clinical interview and a self-rating questionnaire. - Results - At age 25 years, problematic cannabis use was identified in n=28 participants (9.1%). Childhood conduct/oppositional behavior problems were predictive of problematic cannabis use during young adulthood when comorbid symptoms were controlled for. No such effect was found for childhood attention, hyperactivity/impulsivity or internalizing problems. With respect to psychopathological symptoms during adolescence, only attention problems were significantly related to later problematic cannabis use when controlling for comorbidity. - Conclusions - The current study highlights the role of conduct/oppositional behavior problems during childhood and attention problems during adolescence in later problematic cannabis use. It sheds more light on the developmental sequence of childhood and adolescence psychopathology and young adult cannabis use, which is a prerequisite for effective prevention approaches.